2020
DOI: 10.1186/s13075-020-02330-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced BMP-2/BMP-4 ratio in patients with peripheral spondyloarthritis and in cytokine- and stretch-stimulated mouse chondrocytes

Abstract: Background Excessive bone formation in the entheses is one of the features of peripheral spondyloarthritis (SpA). Complex pathological mechanisms connecting inflammation, mechanical stress, and ossification are probably involved. We focused on bone morphogenetic protein (BMP)-2, -4, and -7 as possible mediators of this process. Methods BMP-2, -4, and -7 concentration was measured by ELISA in synovial fluids (SFs) of SpA (n = 56) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In addition, irisin was also able to blunt the catabolic effect of 10 ng/mL IL‐1β and TNF‐α on hTC metabolism and oxidative stress in vitro. In previous studies, such a concentration has proven effective in inducing a catabolic proinflammatory response in hTCs by both cytokines in vitro 23,24 . Indeed, both the addition of irisin to hTCs cultured in proinflammatory conditions and the later introduction of IL‐1β and TNF‐α in a hTC culture preconditioned with irisin resulted in an increase of mitochondrial activity and decrease of NO concentration, until reaching levels encountered with the standard medium alone.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, irisin was also able to blunt the catabolic effect of 10 ng/mL IL‐1β and TNF‐α on hTC metabolism and oxidative stress in vitro. In previous studies, such a concentration has proven effective in inducing a catabolic proinflammatory response in hTCs by both cytokines in vitro 23,24 . Indeed, both the addition of irisin to hTCs cultured in proinflammatory conditions and the later introduction of IL‐1β and TNF‐α in a hTC culture preconditioned with irisin resulted in an increase of mitochondrial activity and decrease of NO concentration, until reaching levels encountered with the standard medium alone.…”
Section: Discussionmentioning
confidence: 94%
“…It is also interesting that Yoda1 did not induce BMP2 in pCH-OA cells to the same extent as in healthy cells, meaning that activation of Piezo1 in OA cells appears to result in lower production of BMP2. Notably, serum and synovial fluid BMP2 levels were shown to be associated with radiographic and symptomatic severity of knee OA, allowing BMP2 to serve as an alternative biochemical parameter for determining the disease severity of primary knee OA [32,33]. Because it was shown that serum BMP-2 levels were higher in patients with knee OA than in healthy controls, our observation of a decrease in BMP2 expression in pCH-OA cells under Yoda1 could be interpreted as a protective effect in OA cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of mouse model with early peripheral spondyloarthritis, it was shown that the BMP-2/BMP-4 ratio increased 6.5 times in the peripheral joints as a result of cytokine induction. 30 In our study, we divided the patients into 2 groups as active and inactive according to their BASDAI scores and examined the level of biomarkers. As a result, BMP-2 values were significantly higher in active disease, while BMP-4 values were significantly lower.…”
Section: Discussionmentioning
confidence: 99%